Work Alienation and Work Engagement. The Mediating Role of Perceived Social Support - Stănescu, Dan Florin; Romașcanu, Marius Constantin (European Journal of Sustainable Development, 2023)
In the present research, we aimed to study the relationship between work alienation and work engagement and the mediating role of perceived social support. The current study used data from 178 participants (48 men and 130 women) aged 21 to 53 years (M=30.88, SD=9.00). Participants were invited to complete the following instruments: Work Alienation Scale (Nair & Vohra, 2009), The Multidimensional Scale of Perceived Social Support (Zimet et al., 1988), and The Utrecht Work Engagement Scale (Schaufeli & Bakker, 2003). Findings indicate that work alienation and work engagement correlate significantly negatively (r=-.755, p<.01). Similarly, work alienation also correlated significantly negatively with perceived social support (r=-.744, p<.01). Also, perceived social support has proven to be an important mediator between work alienation and work engagement (z=-10.17, p<.01). Keywords: work alienation, work engagement, perceived social support, mediation.